1990
DOI: 10.1152/ajprenal.1990.259.2.f297
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine inhibits Na(+)-H+ exchanger activity in renal BBMV by stimulation of adenylate cyclase

Abstract: To determine a renal tubular mechanism for the natriuretic effect of dopamine (DA) and DA-1 agonists, we measured Na(+)-H+ exchange activity (amiloride sensitive) in rat renal cortical brush-border membrane vesicles (BBMV). Renal cortical tissues were preincubated with ligands before BBMV preparation to study Na(+)-H+ exchange activity in the absence of the added ligands that may compete for ion binding sites of the exchanger. DA and DA-1 agonist-inhibited Na(+)-H+ exchange activity was concentration and time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 0 publications
4
140
0
Order By: Relevance
“…It has been previously reported that H89 fully or partially prevented the NHE inhibition induced by 8-Br-cAMP or by factors that increase intracellular cAMP levels (5,(26)(27)(28)(29). Therefore, we analyzed the effect of H89 on the PKA-and EPAC-dependent inhibitions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that H89 fully or partially prevented the NHE inhibition induced by 8-Br-cAMP or by factors that increase intracellular cAMP levels (5,(26)(27)(28)(29). Therefore, we analyzed the effect of H89 on the PKA-and EPAC-dependent inhibitions.…”
Section: Resultsmentioning
confidence: 99%
“…20,29,30 Modulation mechanisms of the response to DA Na + /H + exchanger It is inhibited by the paracrine effect of DA on the proximal tube resulting from D 1 receptors activation, which stimulates adenyl cyclase. 31 However, it can be also inhibited by a mechanism independent of the cAMP generation, directly through the G protein interaction. 32 Another inhibiting mechanism independent of cAMP is that taking place through PLC activation.…”
Section: Role Of Dopamine In Kidney Functionmentioning
confidence: 99%
“…1,2 At the level of the proximal tubule, the overall increase in sodium excretion produced by dopamine and D 1 receptor agonists results from inhibition of Na ϩ ,K ϩ -adenosine triphosphatase (Na ϩ ,K ϩ -ATPase) 3 and the Na ϩ /H ϩ exchanger. 4 Inhibition of Na ϩ ,K ϩ -ATPase by dopamine occurs via a phospholipase C-coupled protein kinase C-linked pathway. 5,6 Stimulation of D 1 receptors leads to inhibition of the Na ϩ /H ϩ exchanger as a result of increased adenosine 3Ј,5Јcy-clic monophosphate formation and subsequently via protein kinase A-mediated phosphorylation.…”
mentioning
confidence: 99%